A SON Enhanced Algorithm for Observed Time Differences Based Geolocation in Real 3G Networks - Vieira, Pedro (2014)
Conferência - 16th International Symposium on Wireless Personal Multimedia Communications (WPMC)- Jun 24-27, 2013